WATER VAPOR ADSORPTION ISOTHERM IN ZEOLITES REGENERATED BY MICROWAVE THERMOXIDATION METHOD - Maxmudov, Inomjon; Ergashev, Oybek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The research work carried out experimental work on the regeneration of synthetic zeolites of type A. Synthetic zeolites used in industry for drying and cleaning natural gas were regenerated by thermal and thermooxidation methods. The structure, adsorption capacity and chemical composition of the regenerated zeolites were studied. Work was carried out to improve the process by accelerating the regeneration by the thermooxidation method using microwaves.